Sanski Hukum Bagi Pelaku Hiperseks yang Mengakibatkan Kekerasan Dalam Rumah Tangga (KDRT) - Yasmin, Aliya; Lubis, Syaddan Dintara (Legal Standing : Jurnal Ilmu Hukum, 2025)
Sexual urges that are very strong and challenging to control are reflected in hypersexuality, which can result in coercion, pressure, or even violent behavior. It can be difficult to recognize and address incidents of domestic violence involving hypersexual behavior. Because sociological juridical normative legal studies explore the meaning of hypersex, hypersexual variables, related cases, and hypersex, these findings help in building legal arguments. The hope is to maintain the welfare of every family member and build a family atmosphere free from sexual violence. Legal writing is included in the category of sociological jurisprudential normative legal research, trying to investigate legal penalties for those involved in hypersexual behavior that leads to sexual violence. Legal norms are the subject of the analysis of the internal perspective of this legal method. Legislation relating to the crime of sexual violence is secondary data referred to by this study. The findings of this study indicate that the elements of punishment for perpetrators of hypersex based on criminal law are a single/imperative formulation system, an alternative formulation system, and a cumulative formulation system. While based on Islamic criminal law, ta'zir punishment is a sanction that can be given to those who commit violations including sexual violence. In addition, the type of ta'zir punishment also differs depending on the choice of the government judge or ulul amri based on ijtihad.